PENGARUH SOFTSKILL DAN HARDSKILL TERHADAP KINERJA KARYAWAN - Rudini Rudini; Muhammad Kasran; Suparni Sampetan (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to determine the effect of soft skills and hard skills in a company. The method applied in this research is the quantitative method, by taking sample data from 100 respondents using the stratified random sampling method, which means that people are not grouped into groups that are not homogeneous and are stratified proportionally. Sig value (2-tailed) which can be concluded from the table. 1 that each item in the Hard Skill variable (X.1), Soft Skill variable (X.2), and Employee Performance variable (Y) can be drawn a real conclusion, it can be concluded that all variables are real because the sig. (2-tailed) < 0.05. The results of the hard skill test show a relevance level of 0.001 based on the hypothesis test. Hard skills have a positive and significant impact on employee performance. Because Ho is not accepted and Ha is accepted based on the reference in this study, with a significance level of less than 0.05